WOMEN STRUGGLE REVEALED IN KRISTIN HANNAHâ€™S THE GREAT ALONE: POSITIONING GENDER IN LEGAL, ECONOMY, AND SOCIAL FIELDS (Sastra Inggris UNPAM, 2022)
The title of this research is â€œWomen Struggle Revealed In Kristin Hannahâ€™s The Great Alone: Positioning In Legal, Economy, and Social Fieldsâ€. The Great Alone novel by Kristin Hannah (2018) discusses the life of a female character, Lenora Allbright who can struggle with a different life than before. She is so patient to face the trials that are happening, the problem raised in this research is how is the issue of women struggle and how does the protagonist survive the problems of gender in legal, economy, and social fields in The Great Alone by Kristin Hannah (2018). The theory used in this research is existential feminism from Simone de Beauvoir (1949). The data analysis approach used by the researcher is descriptive qualitative. The result shows that there are kinds of struggle of women positioning gender in legal, economy, and social. Besides that, the protagonist survive the problems of gender in legal, economy, and social fields. Keyword: descriptive qualitative, existential feminism, gender, and women struggle.